Migrating for Change: How Polish Feminist Activists Turn Oppression into Action Abroad - Muszel, Magdalena (PARTECIPAZIONE E CONFLITTO, 2025)
Over the past decade, feminist activism has significantly expanded globally, responding to increasing gender-based violence and repressive state policies. This article investigates the migration of Polish feminist activists to the UK, specifically examining how oppressive policies targeting reproductive rights, exemplified by Poland's Black Protests and Women's Strike, have influenced their decisions to migrate. Drawing on qualitative research from 21 in-depth interviews, the study uncovers complex migration motivations that blend economic necessity, personal safety, and political defiance. Utilizing "embodied resistance" as a conceptual framework, it argues that migration constitutes a strategic extension of feminist activism, enabling Polish feminists to sustain and expand their advocacy abroad. The study also explores intersectional dimensions of migration, highlighting how race, class, and legal status shape activists' experiences and opportunities for engagement. Ultimately, it contributes to transnational feminist scholarship by reframing migration not merely as escape but as deliberate, politically motivated resistance that reinforces global feminist solidarity and activism. AKNOWLEDGMENTS This article was written as part of the research project “Political Activism of Poles in Great Britain,” conducted at the University of Gdańsk and funded by the National Science Centre (Narodowe Centrum Nauki, Poland), grant no. UMO-2020/37/B/HS6/01748/Z-2020/37/B/HS6/01748/3.